Epoxy resin composite material for copper clad laminate and preparation method thereof
By using toughened isocyanate modified epoxy resin and nanographene oxide/activated graphene composite materials in copper clad plates, the problems of complex process and insufficient performance in the preparation process of existing toughened halogen-free resins are solved, and the problem of insufficient process and insufficient performance in the preparation process is achieved. The copper clad plate has high heat resistance, good tensile performance and excellent dielectric properties.
Patent Information
- Application Number
- CN202410923297.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The existing toughened halogen-free resin requires complex processes and special formulas during the preparation process, which increases production cost and manufacturing difficulty. Its mechanical properties and thermal stability are also limited, such as heat resistance, tensile strength, and thermal expansion coefficient. and insufficient dielectric performance.
Using toughened isocyanate modified epoxy resin, bisphenol A liquid epoxy resin, linear phenolic epoxy resin, diphenylmethane diisocyanate, catalyst, phenol oxygen resin and tetrafunctional phenolic epoxy resin are used as specific Proportionally formulated, combining nanographene oxide and activated graphene, and epoxy resin composite materials for copper clad plates are prepared by ultrasonic dispersion and hot pressing composite technology.
The heat resistance, tensile properties and dielectric properties of epoxy resin are improved, the thermal stability and reliability of copper clad plates are significantly enhanced, the thermal expansion coefficient is reduced, and the glass transition temperature and heat resistance cycles are improved.
Smart Images

Figure CN118702889B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a toughened isocyanate-modified epoxy resin for copper clad laminates and a preparation method thereof, an epoxy resin composite material for copper clad laminates and a preparation method thereof, and a preparation method of a copper clad laminate. Background Art
[0002] With the development of electronic technology, electronic technology is being used more and more widely in all walks of life, and electronic equipment is gradually developing rapidly towards high frequency, high speed, high power and high integration. In the process of printed circuit processing, when drilling small holes, the hole wall overheats. When hot air leveling, infrared reflow soldering and other thermal shocks are carried out during material processing, the copper layer at the corner of the hole wall is prone to breakage and the hole wall shrinkage, resulting in quality problems.
[0003] In practical application, the heating temperature and frequency of circuit boards are constantly increasing, and high heat resistance has become a property that must be considered for copper clad laminate materials. The traditional solution is to develop a resin composition with high thermal stability and impregnate the reinforcing material to make a substrate according to the conventional production process of copper clad laminates, and then cover one or both sides with electrolytic copper foil to laminate into copper clad laminates.
[0004] The researchers have gained a deeper understanding of the molecular structure design, synthesis process and material performance regulation of toughened halogen-free flame-retardant resins. By precisely controlling the polymerization reaction, optimizing the formula and introducing new toughening agents and flame retardants, they have achieved effective regulation of the properties of the resin materials, making them have both excellent flame retardant properties and good toughening effects.
[0005] However, the existing toughened halogen-free resins require complex processes and special formulas during the preparation process, which increases production costs and manufacturing difficulties. Secondly, the mechanical properties and thermal stability of this resin may have certain limitations. At present, most of the methods used to increase the crosslinking density and add inorganic fillers are to enhance the toughness of the resin composition, but the heat resistance, tensile strength, thermal expansion coefficient and dielectric properties are still insufficient and need to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a toughened isocyanate-modified epoxy resin for copper clad laminates and a preparation method thereof, an epoxy resin composite material for copper clad laminates and a preparation method thereof, and a preparation method of a copper clad laminate.
[0007] A toughened isocyanate modified epoxy resin for copper clad laminates, the raw materials of which include: bisphenol A type liquid epoxy resin, linear phenolic epoxy resin, diphenylmethane diisocyanate, a catalyst, phenolic resin, and tetrafunctional phenolic epoxy resin; the mass ratio of the bisphenol A type liquid epoxy resin, linear phenolic epoxy resin, diphenylmethane diisocyanate, the catalyst, the phenolic resin, and the tetrafunctional phenolic epoxy resin is 300-350: 220-300: 70-120: 0.09-0.12: 48-52: 28-32.
[0008] Preferably, the epoxy equivalent of the toughened isocyanate-modified epoxy resin is 250-340 g / mol.
[0009] Preferably, the solid content of the toughened isocyanate-modified epoxy resin is 70-80%.
[0010] Preferably, the catalyst is dibutyltin dilaurate.
[0011] The preparation method of the toughened isocyanate modified epoxy resin for the copper clad laminate comprises the following steps: stirring bisphenol A type liquid epoxy resin and linear phenolic epoxy resin, heating to 75-85°C; adding a catalyst, heating to 120°C; continuing to heat to 160°C, and dropping diphenylmethane diisocyanate during the process of heating from 120°C to 160°C; then adding phenolic epoxy resin, adjusting the temperature to 170±5°C, and reacting for 100-140min; then adding tetrafunctional phenolic epoxy resin, adjusting the temperature to 150±3°C, and reacting for 25-35min, and then adding butanone to dissolve until the solid content is 70-80%.
[0012] A composite epoxy resin material for copper clad laminates, the raw materials of which include, by mass: 10-20 parts of the toughened isocyanate-modified epoxy resin, 1-4 parts of nano graphene oxide, 0.1-0.5 parts of formaldehyde, 0.1-0.2 parts of cyclohexyl isocyanide, 1-2 parts of octylamine, 5-10 parts of tetraethyl orthosilicate, 1-5 parts of graphene, 1-2 parts of saturated ammonia water, 1-2 parts of maleic anhydride, 5-15 parts of solvent, 1-2 parts of curing agent and 0.1-1 part of curing accelerator.
[0013] Preferably, the solvent is at least one of acetone, butanone, propylene glycol methyl ether and N,N-dimethylformamide.
[0014] Preferably, the curing agent is dicyandiamide or 4,4-diaminodiphenyl sulfone.
[0015] Preferably, the curing accelerator is at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole and 2-phenyl-4-methylimidazole.
[0016] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0017] S1. Disperse nano-graphene oxide in water, ultrasonically disperse for 10-30 minutes, adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 60-80° C. for 1-4 hours, add the toughened isocyanate-modified epoxy resin and stir for 5-15 minutes, let stand for 10-30 minutes, and remove the solvent to obtain a pretreated epoxy resin;
[0018] S2, adding tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 1-2 hours, adding saturated ammonia water thereto, continuing ultrasonication for 10-30 minutes, stirring at 70-90° C. for 1-2 hours, adding maleic anhydride thereto under stirring, continuing stirring for 2-4 hours, filtering, washing with water, and vacuum drying to obtain activated graphene;
[0019] S3. Add activated graphene and solvent to the pretreated epoxy resin and stir for 10-30 minutes. Add curing agent and curing accelerator under stirring and continue stirring for 1-5 minutes.
[0020] Preferably, in S1, the ultrasonic dispersion frequency is 5-15 kHz.
[0021] Preferably, in S1, 0.5-1.5 mol / L hydrochloric acid is used to adjust the pH value of the system to 4-5.
[0022] Preferably, in S2, the mass fraction of the ethanol aqueous solution is 40-50%.
[0023] Preferably, in S2, the ultrasonic dispersion frequency is 10-15 kHz.
[0024] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 10-20 seconds, taking it out, curing it at 200-250° C. for 1-5 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, and hot pressing and compounding it at 180-195° C. for 1-2 hours.
[0025] Preferably, the hot pressing pressure is 5-8 MPa.
[0026] Beneficial effects:
[0027] 1. The present invention combines hydrophobic groups on the surface of nano-graphene oxide to make the product amphiphilic. Under the hydrophobic effect, it can self-assemble to form aggregates. Under high shear rate, the intermolecular effect is weakened, the aggregate structure is destroyed, and it can be entangled with the molecular chain structure of the toughened isocyanate-modified epoxy resin and stably coated on the surface of the epoxy resin, which can not only effectively prevent the expansion of the epoxy resin and avoid the generation of more microcracks; but also because the rigidity of the molecular chain is increased, the mobility of the epoxy chain segment is weakened, the degree of cross-linking after curing is greatly improved, the glass transition temperature is effectively increased, the number of heat-resistant cycles is good, and the thermal stability is excellent.
[0028] 2. The present invention combines the deposited silicon dioxide on the graphene surface to obtain activated graphene, and adopts the pretreated epoxy resin as the matrix. The activated graphene has high affinity with the pretreated epoxy resin in the presence of maleic anhydride, which can not only further reduce the thermal expansion coefficient of the copper clad laminate and improve the heat resistance, but also effectively solve the problem that graphene / silicon dioxide is easy to agglomerate in the resin matrix; the maleic anhydride grafted on the activated graphene can be combined with the pretreated epoxy resin, and the product has not only high tensile properties and bending strength, but also excellent dielectric properties. The printed circuit copper clad laminate manufactured using the activated graphene has good reliability and processability and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a comparison chart of the glass transition temperature and oxygen index of sheets made from the epoxy resin composite materials obtained in Example 8 and Comparative Examples 4-5.
[0030] Figure 2 The figure is a comparison chart of the tensile strength and impact strength of sheets made from the epoxy resin composite materials obtained in Example 8 and Comparative Examples 4-5.
[0031] Figure 3 The dielectric properties of the copper clad laminates obtained by using Example 8 and Comparative Examples 4-5 are compared.
[0032] Figure 4 The figure is a comparison chart of the thermal expansion coefficient and the number of heat-resistant cycles of the copper-clad laminates obtained by using Example 8 and Comparative Examples 4-5. DETAILED DESCRIPTION
[0033] The present invention will be further explained below in conjunction with specific embodiments.
[0034] Example 1
[0035] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 350g of bisphenol A liquid epoxy resin and 220g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.12g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 100g of diphenylmethane diisocyanate is added dropwise during the process of heating from 120°C to 160°C; then 50g of phenolic resin is added, the temperature is adjusted to 165°C, and the reaction is carried out for 120min; then 30g of tetrafunctional phenolic epoxy resin is added, the temperature is adjusted to 147°C, the reaction is carried out for 30min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0036] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this example is 303 g / mol.
[0037] Add 25.988g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 150g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this example, mix well, and prepare a resin glue solution with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue solution, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm 3 ×20min) to make copper clad laminate products.
[0038] Example 2
[0039] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 300g of bisphenol A liquid epoxy resin and 250g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.1g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 120g of diphenylmethane diisocyanate is added dropwise during the temperature rise from 120°C to 160°C; then 50g of phenolic resin is added, the temperature is adjusted to 170°C, and the reaction is carried out for 120min; then 30g of tetrafunctional phenolic epoxy resin is added, the temperature is adjusted to 150°C, the reaction is carried out for 30min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0040] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this example is 338 g / mol.
[0041] Add 23.303g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 148.5g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this example, mix well, and prepare a resin glue with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm3 ×20min) to make copper clad laminate products.
[0042] Example 3
[0043] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 300g of bisphenol A liquid epoxy resin and 300g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.12g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 70g of diphenylmethane diisocyanate is added dropwise during the process of heating from 120°C to 160°C; then 50g of phenolic resin is added, the temperature is adjusted to 175°C, and the reaction is carried out for 120min; then 30g of tetrafunctional phenolic epoxy resin is added, the temperature is adjusted to 153°C, the reaction is carried out for 30min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0044] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this example is 258 g / mol.
[0045] Add 30.525g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 152.25g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this example, mix well, and prepare a resin glue with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm 3 ×20min) to make copper clad laminate products.
[0046] Comparative Example 1
[0047] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 200g of bisphenol A liquid epoxy resin and 380g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.12g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 120g of diphenylmethane diisocyanate is added dropwise during the temperature rise from 120°C to 160°C; then 50g of phenolic resin is added, the temperature is adjusted to 170±5°C, the reaction is carried out for 120min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0048] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this comparative example is 329 g / mol.
[0049] Add 23.933g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 149.25g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this comparative example, mix well, and prepare a resin glue solution with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue solution, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm 3 ×20min) to make copper clad laminate products.
[0050] Comparative Example 2
[0051] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 350g of bisphenol A liquid epoxy resin and 220g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.15g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 100g of diphenylmethane diisocyanate is added dropwise during the process of heating from 120°C to 160°C; then 30g of phenolic resin is added, the temperature is adjusted to 170°C, and the reaction is carried out for 120min; then 50g of tetrafunctional phenolic epoxy resin is added, the temperature is adjusted to 150°C, the reaction is carried out for 30min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0052] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this comparative example is 292 g / mol.
[0053] Add 26.97g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 150.75g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this comparative example, mix well, and prepare a resin glue with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm 3 ×20min) to make copper clad laminate products.
[0054] Comparative Example 3
[0055] The toughened isocyanate modified epoxy resin is prepared by the following specific operation: 350g of bisphenol A liquid epoxy resin and 220g of linear phenolic epoxy resin are stirred and the temperature is raised to 80°C; 0.12g of dibutyltin dilaurate is added and the temperature is raised to 120°C; the temperature is further raised to 160°C, and 100g of diphenylmethane diisocyanate is added dropwise during the process of heating from 120°C to 160°C; then 20g of phenolic resin is added, the temperature is adjusted to 170°C, and the reaction is carried out for 120min; then 60g of tetrafunctional phenolic epoxy resin is added, the temperature is adjusted to 150°C, the reaction is carried out for 30min, and butanone is added to dissolve the mixture until the solid content is 75%.
[0056] The epoxy equivalent of the toughened isocyanate-modified epoxy resin obtained in this comparative example is 286 g / mol.
[0057] Add 27.533g of curing agent dicyandiamide, 0.75g of curing accelerator 2-methylimidazole and 150.75g of N,N-dimethylformamide to 1000g of the toughened isocyanate modified epoxy resin obtained in this comparative example, mix well, and prepare a resin glue with a solid content of 60-70%. Dip the glass fiber cloth in the above epoxy resin glue, bake it in an oven at 170℃ to make a semi-cured PP sheet, and then press it into shape with a hot press (hot pressing conditions are 175℃×35kg / cm 3 ×20min) to make copper clad laminate products.
[0058] The copper clad laminates obtained in the above examples 1-3 and comparative examples 1-3 were subjected to performance tests, as follows:
[0059] (1) The glass transition temperature (Tg) of each group of samples was measured according to IPC-TM-6502.4.25.
[0060] (2) The flexural strength of the laminate of each group of samples was tested according to IPC-TM-6502.4.4 method.
[0061] (3) The interlayer adhesion of the laminates of each group of samples was tested according to the axe-edge separation method.
[0062] The results are as follows:
[0063]
[0064] It can be seen from the above table that the performance of the toughened isocyanate-modified epoxy resin obtained in Example 2 is the best, so the toughened isocyanate-modified epoxy resin obtained in Example 2 is used to participate in the preparation of the following epoxy resin composite material for copper clad laminates and copper clad laminates.
[0065] Example 4
[0066] A composite epoxy resin material for copper-clad laminates, the raw materials of which include: 100 g of the toughened isocyanate-modified epoxy resin obtained in Example 2, 10 g of nano-graphene oxide, 1 g of formaldehyde, 1 g of cyclohexyl isocyanate, 10 g of octylamine, 50 g of tetraethyl orthosilicate, 10 g of graphene, 10 g of saturated ammonia water, 10 g of maleic anhydride, 50 g of acetone, 10 g of dicyandiamide, and 1 g of 1-methylimidazole.
[0067] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0068] S1, disperse nano-graphene oxide in 200g water, ultrasonically disperse for 10min, the ultrasonic frequency is 5kHz, use 0.5mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 60°C for 1h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 1000r / min for 5min, let stand for 10min, remove the solvent to obtain a pretreated epoxy resin;
[0069] S2, adding ethyl orthosilicate to 300g of 40% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 1h, the ultrasonic frequency is 10kHz, adding saturated ammonia water thereto, continuing ultrasonication for 10min, stirring at a temperature of 70°C for 1h, adding maleic anhydride thereto under stirring, continuing stirring for 2h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0070] S3. Add activated graphene and acetone to the pretreated epoxy resin, stir at a speed of 50 r / min for 10 min, add dicyandiamide and 1-methylimidazole under stirring, and continue stirring for 1 min.
[0071] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 10 seconds, taking it out, curing it at a temperature of 200°C for 1 minute, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 180°C for 1 hour, and the hot pressing pressure is 5Mpa.
[0072] Example 5
[0073] A composite epoxy resin material for copper clad laminates, the raw materials of which include: 200 g of the toughened isocyanate-modified epoxy resin obtained in Example 2, 40 g of nano-graphene oxide, 5 g of formaldehyde, 2 g of cyclohexyl isocyanate, 20 g of octylamine, 100 g of tetraethyl orthosilicate, 50 g of graphene, 20 g of saturated ammonia water, 20 g of maleic anhydride, 150 g of butanone, 20 g of 4,4-diaminodiphenyl sulfone, and 10 g of 2-phenyl-4-methylimidazole.
[0074] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0075] S1, disperse nano-graphene oxide in 400g water, ultrasonically disperse for 30min, the ultrasonic frequency is 15kHz, use 1.5mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 80°C for 4h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 5000r / min for 15min, let stand for 30min, remove the solvent to obtain a pretreated epoxy resin;
[0076] S2, adding ethyl orthosilicate to 500g of 50% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 2h, the ultrasonic frequency is 15kHz, adding saturated ammonia water thereto, continuing ultrasonication for 30min, stirring at a temperature of 90°C for 2h, adding maleic anhydride thereto under stirring, continuing stirring for 4h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0077] S3. Add activated graphene and butanone to the pretreated epoxy resin, stir at 500 r / min for 30 min, add 4,4-diaminodiphenyl sulfone and 2-phenyl-4-methylimidazole under stirring, and continue stirring for 5 min.
[0078] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 20 seconds, taking it out, curing it at a temperature of 250°C for 5 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 195°C for 2 hours, and the hot pressing pressure is 8Mpa.
[0079] Example 6
[0080] A composite epoxy resin material for copper clad laminates, the raw materials of which include: 120 g of toughened isocyanate-modified epoxy resin obtained in Example 2, 30 g of nano-graphene oxide, 2 g of formaldehyde, 1.7 g of cyclohexyl isocyanate, 13 g of octylamine, 90 g of tetraethyl orthosilicate, 20 g of graphene, 17 g of saturated ammonia water, 12 g of maleic anhydride, 120 g of propylene glycol methyl ether, 13 g of dicyandiamide, and 8 g of 2-phenylimidazole.
[0081] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0082] S1, disperse nano-graphene oxide into 250g water, ultrasonically disperse for 25min, the ultrasonic frequency is 8kHz, use 1.2mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 65°C for 3h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 2000r / min for 12min, let stand for 15min, remove the solvent to obtain a pretreated epoxy resin;
[0083] S2, adding ethyl orthosilicate to 450g of 42% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 100min, the ultrasonic frequency is 11kHz, adding saturated ammonia water thereto, continuing ultrasonication for 25min, stirring at a temperature of 75°C for 100min, adding maleic anhydride thereto under stirring, continuing stirring for 2.5h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0084] S3. Add activated graphene and propylene glycol methyl ether to the pretreated epoxy resin, stir at a speed of 400 r / min for 15 min, add dicyandiamide and 2-phenylimidazole under stirring, and continue stirring for 4 min.
[0085] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 12 seconds, taking it out, curing it at a temperature of 230° C. for 2 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 190° C. for 80 minutes, and the hot pressing pressure is 7 MPa.
[0086] Example 7
[0087] A composite epoxy resin material for copper-clad laminates, comprising raw materials: 180 g of toughened isocyanate-modified epoxy resin obtained in Example 2, 20 g of nano-graphene oxide, 4 g of formaldehyde, 1.3 g of cyclohexyl isocyanate, 17 g of octylamine, 70 g of tetraethyl orthosilicate, 40 g of graphene, 13 g of saturated ammonia water, 18 g of maleic anhydride, 80 g of N,N-dimethylformamide, 17 g of dicyandiamide, and 2 g of 2-ethyl-4-methylimidazole.
[0088] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0089] S1, disperse nano-graphene oxide into 350g water, ultrasonically disperse for 15min, the ultrasonic frequency is 12kHz, use 0.8mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 75°C for 2h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 4000r / min for 8min, let stand for 25min, remove the solvent to obtain a pretreated epoxy resin;
[0090] S2, adding ethyl orthosilicate to 350g of 48% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 80min, the ultrasonic frequency is 13kHz, adding saturated ammonia water thereto, continuing ultrasonication for 15min, stirring at a temperature of 85°C for 80min, adding maleic anhydride thereto under stirring, continuing stirring for 3.5h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0091] S3. Add activated graphene and N,N-dimethylformamide to the pretreated epoxy resin, stir at a speed of 100 r / min for 25 min, add dicyandiamide and 2-ethyl-4-methylimidazole under stirring, and continue stirring for 2 min.
[0092] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 18 seconds, taking it out, curing it at a temperature of 210° C. for 4 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 185° C. for 100 minutes, and the hot pressing pressure is 6 MPa.
[0093] Example 8
[0094] A composite epoxy resin material for copper-clad laminates, the raw materials of which include: 150 g of the toughened isocyanate-modified epoxy resin obtained in Example 2, 25 g of nano-graphene oxide, 3 g of formaldehyde, 1.5 g of cyclohexyl isocyanate, 15 g of octylamine, 80 g of tetraethyl orthosilicate, 30 g of graphene, 15 g of saturated ammonia water, 15 g of maleic anhydride, 100 g of N,N-dimethylformamide, 15 g of dicyandiamide, and 5 g of 2-methylimidazole.
[0095] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0096] S1, disperse nano-graphene oxide in 300g water, ultrasonically disperse for 20min, the ultrasonic frequency is 9kHz, use 1mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 70°C for 2.5h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 3000r / min for 10min, let stand for 20min, remove the solvent to obtain a pretreated epoxy resin;
[0097] S2, adding ethyl orthosilicate to 400g of 45% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 90min, the ultrasonic frequency is 12kHz, adding saturated ammonia water thereto, continuing ultrasonication for 20min, stirring at a temperature of 80°C for 90min, adding maleic anhydride thereto under stirring, continuing stirring for 3h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0098] S3. Add activated graphene and N,N-dimethylformamide to the pretreated epoxy resin, stir at a speed of 300 r / min for 20 min, add dicyandiamide and 2-methylimidazole under stirring, and continue stirring for 3 min.
[0099] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 15 seconds, taking it out, curing it at a temperature of 220° C. for 3 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 188° C. for 90 minutes, and the hot pressing pressure is 6.5 MPa.
[0100] Comparative Example 4
[0101] A composite epoxy resin material for copper-clad laminates, comprising raw materials: 150 g of the toughened isocyanate-modified epoxy resin obtained in Example 2, 25 g of nano-graphene oxide, 80 g of tetraethyl orthosilicate, 30 g of graphene, 15 g of saturated ammonia water, 15 g of maleic anhydride, 100 g of N,N-dimethylformamide, 15 g of dicyandiamide, and 5 g of 2-methylimidazole.
[0102] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0103] S1, disperse nano-graphene oxide into 300g water, ultrasonically disperse for 20min, the ultrasonic frequency is 9kHz, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 3000r / min for 10min, let stand for 20min, remove the solvent to obtain a pretreated epoxy resin;
[0104] S2, adding ethyl orthosilicate to 400g of 45% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 90min, the ultrasonic frequency is 12kHz, adding saturated ammonia water thereto, continuing ultrasonication for 20min, stirring at a temperature of 80°C for 90min, adding maleic anhydride thereto under stirring, continuing stirring for 3h, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0105] S3. Add activated graphene and N,N-dimethylformamide to the pretreated epoxy resin, stir at a speed of 300 r / min for 20 min, add dicyandiamide and 2-methylimidazole under stirring, and continue stirring for 3 min.
[0106] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 15 seconds, taking it out, curing it at a temperature of 220° C. for 3 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 188° C. for 90 minutes, and the hot pressing pressure is 6.5 MPa.
[0107] Comparative Example 5
[0108] A composite epoxy resin material for copper clad laminates, the raw materials of which include: 150 g of toughened isocyanate-modified epoxy resin obtained in Example 2, 25 g of nano-graphene oxide, 3 g of formaldehyde, 1.5 g of cyclohexyl isocyanate, 15 g of octylamine, 80 g of tetraethyl orthosilicate, 30 g of graphene, 15 g of saturated ammonia water, 100 g of N,N-dimethylformamide, 15 g of dicyandiamide, and 5 g of 2-methylimidazole.
[0109] The preparation method of the above-mentioned epoxy resin composite material for copper clad laminate comprises the following steps:
[0110] S1, disperse nano-graphene oxide in 300g water, ultrasonically disperse for 20min, the ultrasonic frequency is 9kHz, use 1mol / L hydrochloric acid to adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 70°C for 2.5h, add the toughened isocyanate-modified epoxy resin obtained in Example 2, stir at a speed of 3000r / min for 10min, let stand for 20min, remove the solvent to obtain a pretreated epoxy resin;
[0111] S2, adding ethyl orthosilicate to 400g of 45% ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 90min, the ultrasonic frequency is 12kHz, adding saturated ammonia water thereto, continuing ultrasonication for 20min, stirring at a temperature of 80°C for 90min, filtering, washing with deionized water, and vacuum drying to obtain activated graphene;
[0112] S3. Add activated graphene and N,N-dimethylformamide to the pretreated epoxy resin, stir at a speed of 300 r / min for 20 min, add dicyandiamide and 2-methylimidazole under stirring, and continue stirring for 3 min.
[0113] A method for preparing a copper clad laminate comprises: completely immersing a glass fiber cloth into the above-mentioned epoxy resin composite material for the copper clad laminate for 15 seconds, taking it out, curing it at a temperature of 220° C. for 3 minutes, and treating it to form a substrate; pasting copper foil on both sides of the substrate, hot pressing and compounding it at a temperature of 188° C. for 90 minutes, and the hot pressing pressure is 6.5 MPa.
[0114] The epoxy resin composite materials obtained in Example 8 and Comparative Examples 4-5 were injected into a mold with a polytetrafluoroethylene surface and cured at a temperature of 220° C. The performance tests of the above groups of epoxy resin composite sheets were performed as follows:
[0115] (1) The glass transition temperature of each group of samples was measured by differential scanning calorimetry (DSC).
[0116] (2) The oxygen index of each group of samples was measured with reference to GB / T 2406.1-2008 “Determination of combustion behavior of plastics by oxygen index method Part 1: Guidance”.
[0117] (3) The tensile strength of each group of specimens was measured in accordance with GB / T 1040.2-2022 “Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics”.
[0118] (4) The notched cantilever beam impact strength of each group of samples was measured with reference to GB / T 1843-2008 “Determination of cantilever beam impact strength of plastics”.
[0119] like Figure 1 and Figure 2 As shown, the glass transition temperature and oxygen index of the epoxy resin composite material obtained in Example 8 are the highest, which proves that the epoxy resin composite material obtained in the present invention has excellent heat resistance; and the tensile strength and impact strength are also the highest, which proves that the epoxy resin composite material obtained in the present invention has excellent mechanical properties.
[0120] The copper-clad laminates (glass fiber cloth weight 25 g / m 2 , thickness is 0.03mm; the mass ratio of glass fiber cloth to each group of epoxy resin composite materials is 80:20; the thickness of electrolytic copper foil on both sides is 40μm) and cut to make each group of samples 50mm×50mm×1mm. The dielectric constant and dielectric loss factor of the copper clad laminate are tested at 25℃×10GHz; and the thermal expansion coefficient and heat resistance cycle (40-250℃) of the copper clad laminate are measured.
[0121] like Figure 3 and Figure 4 As shown, the dielectric constant, dielectric loss factor and thermal expansion coefficient of the copper clad laminate obtained in Example 8 are all the lowest, while the number of heat resistance cycles is the largest, which proves that the copper clad laminate obtained in the present invention has excellent dielectric properties and excellent thermal stability.
[0122] The applicant believes that this is because the present invention combines hydrophobic groups on the surface of nano-graphene oxide, making the product amphiphilic, and can self-assemble to form aggregates under the hydrophobic effect. At high shear rates, the intermolecular effect is weakened, the aggregate structure is destroyed, and the aggregate can be entangled with the molecular chain structure of the epoxy resin and stably coated on the surface of the epoxy resin, which can not only effectively prevent the expansion of the epoxy resin and avoid the generation of more microcracks; but also because the rigidity of the molecular chain is increased, the mobility of the epoxy chain segment is weakened, the degree of cross-linking after curing is greatly improved, the glass transition temperature is effectively increased, the number of heat-resistant cycles is good, and the thermal stability is excellent.
[0123] Meanwhile, the present invention combines the deposited silicon dioxide on the graphene surface to obtain activated graphene, adopts the pretreated epoxy resin as the matrix, and the activated graphene has high affinity with the pretreated epoxy resin in the presence of maleic anhydride, which can not only significantly reduce the thermal expansion coefficient of the copper clad plate and improve the heat resistance, but also effectively solve the problem that graphene / silicon dioxide are easy to agglomerate in the resin matrix; the maleic anhydride grafted on the activated graphene can be combined with the pretreated epoxy resin, the product has not only high tensile performance, but also excellent dielectric performance, and the printed circuit copper clad plate manufactured by using the activated graphene has good reliability and processability, and is suitable for large-scale promotion and application.
[0124] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An epoxy resin composite material for copper clad laminate, characterized in that: The raw materials include, by mass: 10-20 parts of toughened isocyanate-modified epoxy resin for copper clad laminate, 1-4 parts of nano graphene oxide, 0.1-0.5 parts of formaldehyde, 0.1-0.2 parts of cyclohexyl isocyanate, 1-2 parts of octylamine, 5-10 parts of tetraethyl orthosilicate, 1-5 parts of graphene, 1-2 parts of saturated ammonia water, 1-2 parts of maleic anhydride, 5-15 parts of solvent, 1-2 parts of curing agent, and 0.1-1 parts of curing accelerator; The raw materials of the toughened isocyanate modified epoxy resin for copper clad laminates include: bisphenol A type liquid epoxy resin, linear phenolic epoxy resin, diphenylmethane diisocyanate, catalyst, phenolic resin, and tetrafunctional phenolic epoxy resin; the mass ratio of bisphenol A type liquid epoxy resin, linear phenolic epoxy resin, diphenylmethane diisocyanate, catalyst, phenolic resin, and tetrafunctional phenolic epoxy resin is 300-350: 220-300: 70-120: 0.09-0.12: 48-52: 28-32; Prepared by the following steps: S1. Disperse nano-graphene oxide in water, ultrasonically disperse for 10-30 minutes, adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 60-80° C. for 1-4 hours, add toughened isocyanate-modified epoxy resin for copper clad laminate, stir for 5-15 minutes, let stand for 10-30 minutes, and remove the solvent to obtain a pretreated epoxy resin; S2, adding tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 1-2 hours, adding saturated ammonia water thereto, continuing ultrasonication for 10-30 minutes, stirring at 70-90° C. for 1-2 hours, adding maleic anhydride thereto under stirring, continuing stirring for 2-4 hours, filtering, washing with water, and vacuum drying to obtain activated graphene; S3. Add activated graphene and solvent to the pretreated epoxy resin and stir for 10-30 minutes. Add curing agent and curing accelerator under stirring and continue stirring for 1-5 minutes.
2. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The epoxy equivalent of the toughened isocyanate-modified epoxy resin is 250-340 g / mol.
3. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The solid content of the toughened isocyanate modified epoxy resin is 70-80%.
4. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.
5. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The toughened isocyanate modified epoxy resin is prepared by the following steps: stirring bisphenol A type liquid epoxy resin and linear phenolic epoxy resin, heating to 75-85°C; adding a catalyst, heating to 120°C; continuing to heat to 160°C, and dropping diphenylmethane diisocyanate during the process of heating from 120°C to 160°C; then adding phenolic epoxy resin, adjusting the temperature to 170±5°C, and reacting for 100-140min; then adding tetrafunctional phenolic epoxy resin, adjusting the temperature to 150±3°C, reacting for 25-35min, and then adding butanone.
6. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The curing agent is dicyandiamide or 4,4-diaminodiphenyl sulfone.
7. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The curing accelerator is at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole and 2-phenyl-4-methylimidazole.
8. The epoxy resin composite material for copper clad laminate according to claim 1, characterized in that: The solvent is at least one of acetone, butanone, propylene glycol methyl ether and N,N-dimethylformamide.
9. A method for preparing the epoxy resin composite material for copper clad laminate according to any one of claims 1 to 8, characterized in that: The steps include: S1. Disperse nano-graphene oxide in water, ultrasonically disperse for 10-30 minutes, adjust the pH value of the system to 4-5, add formaldehyde, cyclohexyl isocyanide and octylamine under stirring, stir at 60-80° C. for 1-4 hours, add toughened isocyanate-modified epoxy resin for copper clad laminate, stir for 5-15 minutes, let stand for 10-30 minutes, and remove the solvent to obtain a pretreated epoxy resin; S2, adding tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adding graphene thereto and ultrasonically dispersing for 1-2 hours, adding saturated ammonia water thereto, continuing ultrasonication for 10-30 minutes, stirring at 70-90° C. for 1-2 hours, adding maleic anhydride thereto under stirring, continuing stirring for 2-4 hours, filtering, washing with water, and vacuum drying to obtain activated graphene; S3. Add activated graphene and solvent to the pretreated epoxy resin and stir for 10-30 minutes. Add curing agent and curing accelerator under stirring and continue stirring for 1-5 minutes.
10. The method for preparing the epoxy resin composite material for copper clad laminate according to claim 9, characterized in that: In S1, the ultrasonic dispersion frequency is 5-15 kHz.
11. The method for preparing the epoxy resin composite material for copper clad laminate according to claim 9, characterized in that: In S1, the pH value of the system is adjusted to 4-5 using hydrochloric acid with a concentration of 0.5-1.5 mol / L.
12. The method for preparing the epoxy resin composite material for copper clad laminate according to claim 9, characterized in that: In S2, the mass fraction of the ethanol aqueous solution is 40-50%.
13. The method for preparing the epoxy resin composite material for copper clad laminate according to claim 9, characterized in that: In S2, the ultrasonic dispersion frequency is 10-15 kHz.
14. A method for preparing a copper clad laminate, characterized in that: include: The glass fiber cloth is completely immersed in the epoxy resin composite material for copper clad laminates as claimed in any one of claims 1 to 8 for 10 to 20 seconds, taken out, cured at 200 to 250° C. for 1 to 5 minutes, and processed to form a substrate; copper foil is attached to both sides of the substrate, and hot-pressed at 180 to 195° C. for 1 to 2 hours.
15. The method for preparing a copper clad laminate according to claim 14, characterized in that: The hot pressing pressure is 5-8MPa.
Citation Information
Patent Citations
Modified epoxy resin for solvent-free copper-clad plate manufacturing procedure as well as preparation and application thereof
CN106986980A
High heat conductivity toughened resin composition and application thereof
CN109135652A